Patterns of belatacept use and risk of post-transplant lymphoproliferative disorder in US kidney transplant recipients: An analysis of the Organ Procurement and Transplantation Network database. - Wida S Cherikh; Tzuyung Douglas Kou; Julia Foutz; Timothy J Baker; Andres Gomez-Caminero (PLoS ONE)
Background Belatacept is approved for the prophylaxis of organ rejection in Epstein-Barr virus (EBV)-seropositive kidney transplant recipients and is associated with a risk of post-transplant lymphoproliferative disorder (PTLD). Methods Data from the Organ Procurement and Transplantation Network were used to examine patterns of belatacept use, describe patient characteristics, and estimate risk of PTLD in EBV-seropositive, kidney-only transplant recipients receiving belatacept- or calcineurin inhibitor (CNI)-based immunosuppression as part of US Food and Drug Administration-mandated safety monitoring. Results During the study period (June 15, 2011-June 14, 2016), 94.9% (1631/1719) of belatacept-treated and 89.7% (59,992/66,905) of CNI-treated patients with known EBV serostatus were EBV seropositive. Among EBV-seropositive patients, 50.2% (belatacept) and 56.8% (CNI) received a standard criteria donor kidney, 59.5% and 18.7% received basiliximab induction, and 22.9% and 50.8% received antithymocyte globulin induction. PTLD developed in nine belatacept-treated patients (two with central nervous system [CNS] involvement) and 225 CNI-treated patients (nine with CNS involvement). Four and 81 patients, respectively, died due to PTLD. Kaplan-Meier analysis did not show a significant between-group difference in PTLD estimated incidence rates within 5 years (0.70% versus 0.48%, respectively; p = 0.18). Additionally, estimated PTLD incidence was not significantly different between treatment groups in a propensity score matched cohort. Conclusions The majority of adult kidney-only transplant recipients treated with belatacept in routine clinical practice are EBV seropositive. In this study, the risk of PTLD in these patients, while higher than for CNI-based immunosuppression, remained low after adjusting for differences in patient characteristics. Trial registration These studies are registered at ClinicalTrials.gov: NCT01670058 and NCT01656343.